2002
DOI: 10.1093/oxfordjournals.jbchem.a003125
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change of Ribosomes during Apoptosis: Degradation and Externalization of Ribosomal Proteins in Doxorubicin-Treated Jurkat Cells

Abstract: Changes in the amount and localization of human ribosomal proteins during apoptosis were determined. When total lysates of Jurkat cells undergoing apoptosis induced by doxorubicin were analyzed by Western blotting, degradation of three ribosomal proteins, S18, L5, and L14, was detected at 48 h after the induction of apoptosis. Decreases in the amounts of these three ribosomal proteins were also observed in ribosome-enriched fractions. These changes were partly abolished by the addition of the pan-caspase inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Because doxorubicin also causes RNA damage 10 and inhibits DNA and RNA synthesis, 11,12 it is not unexpected that doxorubicin would also inhibit the synthesis of proteins. 13,14 In addition to inhibition of protein translation, doxorubicin induces the activation of SAPKs in a number of normal cell types, including hepatocytes, 6 primary mouse macrophages 7 and cardiomyocytes. 8,9 Our work presented here demonstrates that doxorubicin inhibits protein synthesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because doxorubicin also causes RNA damage 10 and inhibits DNA and RNA synthesis, 11,12 it is not unexpected that doxorubicin would also inhibit the synthesis of proteins. 13,14 In addition to inhibition of protein translation, doxorubicin induces the activation of SAPKs in a number of normal cell types, including hepatocytes, 6 primary mouse macrophages 7 and cardiomyocytes. 8,9 Our work presented here demonstrates that doxorubicin inhibits protein synthesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Martelli et al (2000) reported that some nucleolar antigens (namely, PARP-1 and UBF) are cleaved during apoptosis, whereas others (fibrillarin, B23 and C23) are not; cleavage of topoisomerase I and B23 has been shown to occur in cis-DDP-induced apoptosis (Horky et al, 2001). Some autoantigens, such as ribosomal RNPs, previously described to resist proteolysis (Wu et al, 2001) have recently been shown to be cleaved and expressed at the cell surface: six proteins (S15, P0, L5, L6, L36a, L41) have been found to follow this pathway (Nishida et al, 2002). Nucleolin is one of the most studied protein in the nucleolus and it has recently been reported (Mi et al, 2003) to decrease in UV-induced apoptosis, in parallel with PARP-1 degradation.…”
Section: Nucleoplasmic and Nucleolar Rnps In Apoptosismentioning
confidence: 99%
“…However, the immunohistochemical (IHC) localization of ribosomal proteins in colorectal mucosa and cancer was largely unknown due to the limited availability of antibodies specific for human ribosomal proteins. In this study we have demonstrated the expression profile of 12 ribosomal proteins including Sa, S8, S11, S12, S18, S24, L7, L13a, L18, L28, L32, and L35a in human normal colorectal mucosa by IHC using a well-characterized antibody panel for the ribosomal proteins (Nadano et al 2000;Nishida et al 2002). We compared their expression patterns with those in colorectal adenocarcinoma cells.…”
mentioning
confidence: 96%